Bruce Bronzan Press Conference re Candidate for 31st Assembly District at Fresno Hilton Hotel - Watkins, Howard::::::::: (1982)
Supporters in audience: Hilary Ross, ?, ?; Back Row: Judy Ganulin, Victor Salazar, Olga Salazar, ?